2016
DOI: 10.4236/gep.2016.410004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metals Contamination in Sediments of the Vridi Canal (Côte d’Ivoire)

Abstract: The concentrations of cadmium, copper, lead and zinc in sediment samples from the Vridi Canal (Harbour area of economic capital of Cote d'Ivoire) were determined to evaluate the level of contamination. All metal concentrations in sediment samples, except Cu, were greater than the concentration of Upper Continental Crust (UCC). Sediment pollution assessment was undertaken by using Enrichment Factor (EF), geoaccumulation index (I geo ) and Pollution Load Index (PLI). The enrichment factor (Cd: EF = 20.04; Pb: EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…Enrichment is a method used to estimate the anthropogenic impact on sediments by calculating the difference between the metals originating from human activities and those from natural provenance. Enrichment factor is a means of determining anthropogenic influence on heavy metal concentration in sediments (Rodrigue et al, 2016). The EF is calculated by using Equation 1 EF > 40, extremely high enrichment (Sutherland, 2000).…”
Section: Enrichment Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Enrichment is a method used to estimate the anthropogenic impact on sediments by calculating the difference between the metals originating from human activities and those from natural provenance. Enrichment factor is a means of determining anthropogenic influence on heavy metal concentration in sediments (Rodrigue et al, 2016). The EF is calculated by using Equation 1 EF > 40, extremely high enrichment (Sutherland, 2000).…”
Section: Enrichment Factormentioning
confidence: 99%
“…Heavy metals may be introduced into the aquatic environment through natural sources such as atmospheric deposition and geological weathering or by anthropogenic sources including municipal and industrial discharges and agricultural run-off (Savadi et al, 2015;Kanchana et al, 2014). Upon their release into the aquatic environment, heavy metals eventually become deposited in se- Sediments are the major repository of heavy metals in aquatic systems and play a vital role in remobilization and enrichment of the overlying water column (Banerjee et al, 2017;Rodrigue et al, 2016). The concentration of heavy metals in sediments may be 3 -5 times higher than that of the water column with the concentration being influenced by physicochemical adsorption, physical accumulation and biological uptake (Banerjee et al, 2017;El-Madani & Hacht, 2017;Akan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is vital to the existence of all living organisms [1][2][3][4]. However, this valued resource is increasingly being threatened by human population's growth and anthropogenic activities such as mining activity.…”
Section: Introductionmentioning
confidence: 99%
“…The research indicated that mining and the smelting activities caused great destruction to the water environment. The heavy metals are difficult to clear away from the natural environment, or even form a secondary pollution [3][4][5].…”
Section: Introductionmentioning
confidence: 99%